A combination of Wnt and growth factor signaling induces Arl4c expression to form epithelial tubular structures. (21st February 2014) - Matsumoto, Shinji; Fujii, Shinsuke; Sato, Akira; Ibuka, Souji; Kagawa, Yoshinori; Ishii, Masaru; Kikuchi, Akira
Synopsis <boxed-text content-type="graphic" id="embj201386942-blkfxd-0003" position="anchor" orientation="portrait"> </boxed-text> Wnt and EGF signals jointly induce the small GTP‐binding protein Arl4c in epithelial cells, which form tubules. Arl4c regulates actin cytoskeleton dynamics through RhoGTPases, and the resulting cell shape changes activate the transcription factor YAP/TAZ, promoting cell proliferation. Co‐stimulation of epithelial cells with Wnt3a and EGF activates Arl4c, which induces tubule formation. Arl4c regulates actin cytoskeleton dynamics through the ARNO‐Arf6‐Rac1‐RhoA axis. Actin cytoskeleton changes activate YAP/TAZ signaling and cell proliferation. This mechanism is involved in the morphogenesis of kidney ureteric buds.